Case report: Acute ischemic stroke caused by intracranial artery dissection in a patient with skull fractures - Zheng, Bo; Luo, XiaoLan; Zhou, JiangHao; Huang, XueQiong; Li, MaoXia; Zheng, Hui; Yuan, YiPing; Wang, Jian (Frontiers in Neurology, 2022)
The intracranial artery dissection (IAD) is an uncommon but life-threatening disease. The IAD would develop a significant cerebral infarction due to unrecognized contrecoup brain injury. We report a 53-year-old man fell to develop blunt cerebrovascular injuries (BCVIs) more than 2 months ago. During his rehabilitation, he often had a transient left headache and underwent short-term right limb weakness twice, but he didn't care. He was hospitalized again because of suffering right limb weakness for more than 4 hours. The brain computed tomography angiography (CTA) showed subtotal occlusion of the left middle cerebral artery M1 segment, and the vascular morphology displayed the IAD. The patient was then treated with balloon dilation and a self-expanding stent. This case highlights that IAD may show delayed onset with no initial typical symptom. By early detecting of abnormal signs and symptoms, serious traumatic brain injury may be avoided.